Cruris Fracture among Child Patients in Dr. Hasan Sadikin General Hospital Bandung - Wenny Dwi Chandra; Yoyos Dias Ismiarto; Alwin Tahid; Nucki Nursjamsi Hidayat (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Cruris are lower extremity fractures commonly found in children. These dangerous fracturesmay alter the quality of life of the patients. This study was conducted to explore the characteristics of crurisfractures in children.Methods: A descriptive cross-sectional study was performed by reviewing the medical records of childrenwho were hospitalized at the Department of Orthopaedi and Traumatology, Dr. Hasan Sadikin GeneralHospital Bandung during 2010–2011.Results: On two years study, 62 cases have been reported. Most cases occurred among senior high schoolgroup (37.1%). Boys (71.0%) have a higher rate of fractures than girls. Fractures most frequently occurredby traffic accidents (87.1%). The fractures are mostly open (58.1%). The common fracture site was tibia(50.0%) rather than fibula (3.2%) and the most frequent location was on the right side (79.0%) and on themiddle third of the leg (41.9%). Majority of the patients went home in good condition (79.0%).Conclusion: Fractures are most frequently occurred in April because of high humidity. The causes anddistribution of the fractures based on diagnosis were related to another study. Furthermore, additionalstudies are needed to explore the characteristics of cruris fracture among children, not only in certainhospital but also in Indonesia especially in West Java.[AMJ.2015;2(1):276–80]